Aldehyde N, N-dimethylhydrazone-based fluorescent substrate for peroxidase-mediated assays. Issue 14 (21st March 2022) - Yoo, Soyeon; Kim, Sudeok; Jeon, Sangyeon; Han, Min Su
Abstract : A fluorescent peroxidase substrate is devised based on aldehyde N, N -dimethylhydrazone with no over-oxidation by excess H2 O2, high photo stability, and wide operating pH. Abstract : Numerous assays based on peroxidase activity have been developed for the detection of analytes due to the various optical peroxidase substrates. However, most substrates are sensitive to light and pH and are over-oxidized in the presence of excess H2 O2 . In this study, 2-((6-methoxynaphthalen-2-yl)methylene)-1, 1-dimethylhydrazine (MNDH ), a fluorescent peroxidase substrate prepared from naphthalene-based aldehyde N, N -dimethylhydrazone, was developed. MNDH showed quantitative fluorescence changes with respect to the H2 O2 concentration in the presence of horseradish peroxidase (HRP), and the MNDH /HRP assay showed no changes in fluorescence caused by over-oxidation in the presence of excess H2 O2 . Further, MNDH was thermo- and photostable. Additionally, the assay could be operated over a considerably wide pH range, from acidic to neutral. Moreover, MNDH can be used to detect glucose quantitatively in human serum samples by using an enzyme cascade assay system.